Risk and protective factors for interpersonal revictimization in people with post-traumatic stress symptoms: a systematic review - Kühner, Christin; Verdaasdonk, Inez; Christ, Carolien; Goudriaan, Anneke E.; Thomaes, Kathleen; de Waal, Marleen (Frontiers in Psychology, 2025)
IntroductionPeople suffering from a psychiatric disorder are at increased risk of being the victim of repeated interpersonal victimization (i.e., revictimization). A psychiatric disorder that has been investigated as both a risk factor and a consequence of interpersonal revictimization is post-traumatic stress disorder (PTSD). However, to date no systematic review has provided an exclusive overview of longitudinally assessed risk or protective factors for interpersonal revictimization in the context of PTSD. With this systematic review, we aim to provide an overview of (a) which facets of PTSD are risk factors for interpersonal revictimization, and (b) which non-PTSD factors are risk or protective factors for interpersonal revictimization?MethodsFollowing our pre-registered systematic search of PubMed, APA PsycInfo, PTSDpubs, Web of Science, and Scopus, we screened N = 1,286 and included N = 16 longitudinal studies.ResultsIn the majority of the studies, the overall severity of PTSD symptoms emerged as a risk factor, while the evidence remained mixed for the severity of hyperarousal and negative changes in mood and cognition. We found no evidence that the severity of intrusion, avoidance, or dissociation are risk factors for interpersonal revictimization. For the non-PTSD risk factors, a majority of studies indicated that the severity of prior victimization and drug use were associated with revictimization. The results remained mixed for problematic alcohol use, childhood maltreatment, depression and maladaptive coping. The protective factors, social support and adaptive coping, did not consistently reduce revictimization.DiscussionPTSD symptom severity was a consistent predictor of revictimization; consequently, reducing PTSD symptom severity as quickly as possible may decrease risk for revictimization. Additional factors to address during intervention are discussed. The study has several limitations, such as the overrepresentation of female participants and the reliance on convenience samples, particularly those involving women residing in shelters. Additionally, there was a disproportionate focus on intimate partner violence (IPV) and sexual abuse as forms of revictimization. Furthermore, we observed considerable heterogeneity in the operationalization and measurement of PTSD (symptoms) and revictimization. Implications of this study are that reducing PTSD symptoms and drug use may decrease risk for future revictimization.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023446788.